Shear strength of concrete beams reinforced with glass fiber reinforced polymer bars without stirrups - Omar Imohamed, Imohamed Ali (2018)
The use of fiber reinforced polymer (FRP) bars as an alternative to steel bars for reinforced concrete (RC) structures is gaining acceptance among the structural engineers. The investigation of structure performance of FRP-RC members has become a critical issue. Extensive researches have been conducted to investigate the shear behavior of RC members with FRP bar. However, the shear strength design of FRPRC beams is similar to that of RC beams with steel bar except that the mechanical properties of FRP bars which affect the shear strength design shall be considered. The focus of this research is to investigate the shear behavior of FRP-RC beams. A total of 18 RC beams were constructed and tested up to failure, the test beams included 10 GFRP-RC beams and 8 steel-RC beams. In order to realize the occurrence of the shear failure, all tested beams were designed without stirrups. The test variables were the reinforcement ratio (p), shear span to depth ratio (aid), depth of beam (d), and concrete compressive strength(//). The test results revealed that there is an effect of the variables on the shear behavior of the beams. Finite element model (FEM) was carried out to validate the experimental results conducted in the current investigation, resulting in a good agreement with experiments. The test results were compared with predictions provided by the different available codes, manuals, and design guidelines such as CSA S806-02, ACI 440.1 R-06, JSCE (1997), ISIS M03-07 and theoretical models from Kazemi & Broujerdian (2006), Yousif (2015), Chowdhury et al. (2016) and Mihaylov (2016), in which it was observed from the statistical analysis that Kazemi & Broujerdian (2006) method showed a good consistency in its differences of percentage compared with other models, particularly for GFRP-RC beams. Based on the obtained experimental results, a proposed modification to the Kazemi & Broujerdian (2006) equation is presented and verified against test results available in the literature. It was found that the proposed equation is more accurate and consistent in predicting the shear strength ofGFRP-RC beams.